2011
DOI: 10.1002/mus.22255
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of non–length‐dependent small‐fiber sensory neuropathy

Abstract: NLD-SFSN is more common in women, presents at a younger age, and is more likely to be associated with immune-mediated conditions than LD-SFSN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 23 publications
7
107
3
1
Order By: Relevance
“…The most commonly etiology reported for SFN is diabetes mellitus 2,4. Other possible etiologies include impaired glucose tolerance (IGT),5,6 connective tissue disease,7,8 celiac disease,9 thyroid dysfunction,10,11 vitamin B12 deficiency,10 monoclonal gammopathy,12,13 HIV and hepatitis C infections,14,15 amyloidosis,16 toxicity due to alcohol or drugs,17,18 and hereditary neuropathies 19. Despite knowledge of these factors, the reported etiology of SFN has remained unclear in 23-93% of investigated patients 1,4,13,20.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly etiology reported for SFN is diabetes mellitus 2,4. Other possible etiologies include impaired glucose tolerance (IGT),5,6 connective tissue disease,7,8 celiac disease,9 thyroid dysfunction,10,11 vitamin B12 deficiency,10 monoclonal gammopathy,12,13 HIV and hepatitis C infections,14,15 amyloidosis,16 toxicity due to alcohol or drugs,17,18 and hereditary neuropathies 19. Despite knowledge of these factors, the reported etiology of SFN has remained unclear in 23-93% of investigated patients 1,4,13,20.…”
Section: Introductionmentioning
confidence: 99%
“…However, occasionally, SFN may present with an asymmetrical patchy pattern of sensory symptoms starting in the arms or even in the face, which suggest a non-length-dependent ganglionopathy. [4][5][6] In up to 47% of cases, no underlying cause is revealed at the time point of diagnosis, 7 therefore these cases are classified as "idiopathic." Making the diagnosis of SFN often poses a challenge because routine electrophysiological measures remain normal.…”
mentioning
confidence: 99%
“…It has been suggested that hyperactivity of small, unmyelinated C-fibers results in hyperalgesia and allodynia (36). Also, Khan et al (38) reported that A-fiber afferents in diabetic rats developed abnormal spontaneous discharges and increased sensitivity to mechanical stimuli, suggesting a role of large A-fiber neurons in addition to nociceptive C-fibers in the development of diabetic neuropathic pain in early stage of DM. In our opinion, according to results of previous studies in the literature, a few weeks after induction of hyperglycemia, there is an increased expression and/or activation of Na v Chs that play an important role on developing of hyperexcitability in early stage of DM, but the possible role of Na v Chs on occured hypoexcitability and hyposensation as major symptoms of the later stage of DM 6-8 weeks after induction of hyperglycemia is still unknown.…”
Section: Discussionmentioning
confidence: 99%